Clinical Manifestations, Proposed Mechanisms, and Updated Management of Severe Atopic Dermatitis and Associated Pruritus. Issue 1 (5th January 2022) - Kirchner, Allison; Lake, Eden
ABSTRACT: Atopic dermatitis (AD) is defined as a chronic inflammatory skin disease characterized by pruritus and xerosis. AD is the most common inflammatory skin disease, affecting about 200 million people worldwide. Although AD is diagnosed in all ages and races, there are distinct findings associated with the different age groups that can help guide the diagnosis. Recent, robust studies have identified hereditary and genetic risk factors, which have guided the treatment options for AD. This includes various topical agents, a new generation of systemic biologics (dupilumab, tralokinumab, and lebrikizumab), and Janus kinase inhibitors (abrocitinib and baricitinib). Here, we describe some of the common clinical manifestations, hypothesized mechanisms, and current therapeutic treatment options for patients with moderate-to-severe AD.